61 old father and grandfather obtained Executive Masters’ from UMP - UMP, PNC (2018)
Mohamed Hamdan A Aziz, 61, thirst for education has never ceased to fade, the burning yearning perhaps stemmed from not being able to pursue his studies when he was younger because their livelihood only depended on his father who was a rubber tapper.